A review of error correction procedures during instruction for children with developmental disabilities. Issue 2 (23rd November 2018) - Cariveau, Tom; La Cruz Montilla, Astrid; Gonzalez, Elizabeth; Ball, Sydney
Abstract : Error correction procedures are remedial strategies presented following an incorrect response that increases the probability that a correct response will occur in the future. Error correction is commonly used during skill acquisition programs for children with developmental disabilities; however, the specific strategy used may differ considerably. Recent comparative studies have examined the effect of numerous error correction procedures on the efficiency of acquisition for children with developmental disabilities. Despite considerable merit, minor procedural differences and unique terms for similar procedures likely affect comparisons across studies. Here, we clarify the procedures and findings of these studies and suggest areas of future research.